Metabolite profiling of fermented milks as affected by adjunct cultures during long-term storage - Isık, Sumeyra; Dagdemir, Elif; Tekin, Ali; Hayaloglu, Ali Adnan (Elsevier Ltd, 2023)
The effects of starter strains (Lactiplantibacillus plantarum 156, Lactobacillus casei ATCC 334, Lactobacillus helveticus DPC 4571, and Streptococcus thermophilus 20S4) on the physicochemical and microbiological properties, volatiles, bioactive peptides, and gamma-aminobutyric acid (GABA) contents of fermented milks were evaluated during storage. The use of different adjunct culture combinations had no significant effect on the gross chemical composition. The bacterial strains remained highly viable in the fermented milk during storage. The peptide extracts exhibited a high ACE-inhibitory activity, which was particularly increased in the samples where L. casei ATCC 334 and L. helveticus DPC 4571 strains co-existed. Almost the same levels of antioxidant activity was observed in the peptides extracted from fermented milk. Peptide extracts showed a certain level of antimicrobial activitiy against Staphylococcus aureus ATCC 29213, Listeria monocytogenes ATCC 7644, Salmonella Typhimurium RSHMB 95091, and Escherichia coli O157:H7; however, no inhibitory activity was observed against Bacillus cereus BC 6230. Among the free amino acids, His, Arg, Ala, and Pro were predominant in the samples. Significant differences were observed between samples regarding GABA content, which increased with increasing levels of proteolytic activity. A total of 33 volatile compounds were identified in fermented milks, with acetone, 2,3-butanedione, acetoin, 2-heptanone, acetic and hexanoic acids being the predominant volatiles. These results demonstrate the multifunctional role of peptides and GABA extracted from fermented milk through the action of specific Lactobacillus strains. Therefore, such a functional fermented milk product can be used to reduce the risk of disease or improve specific physiological functions. © 2023 Elsevier Ltd
Keywords: Bioactive peptide; Gamma aminobutyric acid; Volatiles; Yogurt-like fermented milk